Infection of Human Dental Pulp Stromal Cells by Streptococcus mutans: Shedding Light on Bacteria Pathogenicity and Pulp Inflammation - Maisonneuve, Elodie; Chevrier, Julie; Dubus, Marie; Varin, Jennifer; Sergheraert, Johan; Gangloff, Sophie C.; Reffuveille, Fany; Mauprivez, Cédric; Kerdjoudj, Halima (Frontiers in Cell and Developmental Biology, 2020)
Cariogenic Streptococcus mutans (S. mutans) is implicated in the dental pulp necrosis but also in cardiovascular tissue infections. Herein, the purpose was to elucidate how human dental pulp derived stromal cells (DPSCs) react towards a direct interaction with S. mutans. DPSCs were challenged with S. mutans. Following 3 h of interaction, DPSCs were able to internalize S. mutans (rate < 1 %), and F-actin fibers played a significant role in this process. S. mutans persisted in the DPSCs for 48 h without causing a cytotoxic effect. S. mutans was however able to get out of the DPSCs cytoplasm and to proliferate in the extracellular environment. Yet, we noticed several adaptive responses of bacteria to the extracellular environment such as a modification of the kinetic growth, the increase in biofilm formation on type I collagen and polyester fabrics, as well as a tolerance towards amoxicillin. In response to infection, DPSCs adopted a proinflammatory profile by increasing the secretion of IL-8, lL-1b and TNF-a, strengthening the establishment of the dental pulp inflammation. Overall, these findings showed a direct impact of S. mutans on DPSCs, providing new insights into the potential role of S. mutans in infective diseases.